Separation of Simultaneous Multi-Person Noncontact Physical Activity Signals Using Frequency-Modulated Continuous-Wave Radars - Varela, Victor G. R.; Rodrigues, Davi V. Q.; Li, Changzhi (IEEE Topical Conference on Wireless Sensors and Sensor Networks (Online), 2022)
Portable microwave radars are an emerging technology for remote recognition of human movements such as gesture commands, gait, and physical activities. Existing radar-based works on noncontact physical activity monitoring do not consider extracting individual signals from multiple targets doing exercises simultaneously when illuminated by the same radar sensor, which might be very useful in realistic environments where several people exercise nearby. In this work, the radar-based remote recognition of two human subjects simultaneously doing different exercises is proposed. Also, a strategy to find the range bins associated with the two targets of interest is detailed. Experimental results demonstrate that it is possible to detect and differentiate the exercises performed by each subject and count their corresponding number of exercise repetitions.